Key Concepts and Issues in Nursing Ethics - Scott, P. Anne (Springer International Publishing : Imprint: Springer, 2017)
Short case studies, based on real stories from the health care arena, ensure that each chapter of this book is rooted in descriptions of nursing practise that are grounded, salient narratives of nursing care. The reader is assisted to explore the ethical dimension of nursing practice: what it is and how it can be portrayed, discussed, and analysed within a variety of practice and theoretical contexts. One of the unique contributions of this book is to consider nursing not only in the context of the individual nurse - patient relationship but also as a social good that is of necessity limited, due to the ultimate limits on the nursing and health care resource. This book will help the reader consider what good nursing looks like, both within the context of limitations on resources and under conditions of scarcity. Indeed, any discussion of ethical issues in nursing should be well grounded in a conceptualisation of nursing that nursing students and practising nursing can recognise, accept and engage with. Nursing, like medicine, social work and teaching has a clear moral aim - to do good. In the case of nursing to do good for the patient. However it is vital that in the pressurised, constrained health service of the 21st century, we help nurses explore what this might mean for nursing practice and what can reasonably be expected of the individual nurse in terms of good nursing care.
Keywords: Medicine.; Ethics.; Public health.; Nursing.; Practice of medicine.; elektronické knihy; electronic books